Adaptive divergence and post-zygotic barriers to gene flow between sympatric populations of a herbivorous mite - Ernesto Villacis-Perez (Nature Portfolio, 2021)
Villacis-Perez et al. describe the existence of and the mechanisms sustaining a host race of the spider mite Tetranychus urticae, which was previously regarded as a generalist. Here, the authors identify a specialist host race exhibiting reproductive incompatibility with sympatric generalist populations, as well as significant differences in host performance.